The impact of competition in physical activity and sport on the self-perception of individuals with physical disabilities [Vliv soutěžení při pohybové aktivitě a sportu na sebehodnocení jedinců s tělesným postižením] - Erik Sigmund; Michael Cocquyt (Palacky University, 2011)
BACKGROUND: Physical activity has traditionally been treated as one of many strategies to improve an individual's quality of life. Until fairly recently, this presumption has been accepted as truth and little research has been done on proving or disproving the claim. Now, there has been a larger focus on it and numerous studies have analyzed the contribution physical activity has on the individual's quality of life in all areas. OBJECTIVE: This study analyzes the current literature in the area of physical activity and sport as related to self-perception and the overall quality of life in individuals with physical disabilities. METHODS: Using the websites of the following literature databases: Pubmed, Sport Discus, Medline, APAQ archives, and European Journal of Adapted Physical Activity archives, articles from 1990-2009 were selected based on their focus on analyzing the relationship of self-perception and quality of life to physical activity and sport for individuals with physical disabilities. Using these mentioned search programs, 274 articles were found using the keywords for this article. Of these, 40 articles were chosen for being applicable to the topic and target population. Nine of these articles were then used in the direct results as others were used for anecdotal or background information, due to their lack of consistent terminology. Without consistent terminology it was not possible to use these anecdotal articles to make proper comparisons of results. These trends, from the remaining nine articles were then compared to studies with able-bodied populations. RESULTS: The authors found that, overall, there is a significant positive relationship between physical activity and sport programs on the one hand, and increased self-perception among individuals with physical disabilities on the other. This increase can be seen in the process of the comparison of the individual constructs of self-perception as well as of the differences in self-perception as a whole. Quality of life was also seen, in some studies, to be an additional reference for comparison. The inclusion of competition had no significant effect on these relationships of selfperception. However, individuals competing at an elite or world class level showed significantly higher self-perception than all other groups. When able-bodied studies were compared, similar trends were found in both overall difference in self-perception and differences seen between competition levels. CONCLUSIONS: Findings show that competition should be included in physical activity and sport programs, for individuals with physical disabilities, only if it results in an increase in positive experiences for the participants. Participation in physical activity and sport programs contribute to an improvement in the quality of life of individuals with physical disabilities. [VÝCHODISKA: Zapojení do pohybové aktivity je jednou z tradičních strategií ke zlepšení kvality lidského života. Aplikování této strategie je již hodně publikačně doloženo. Proto bude příspěvek pohybové aktivity ke kvalitě života, sebevnímaní a sebehodnocení obsahem předložené práce. CÍLE: Cílem studie bylo analyzovat současné publikace hodnotící vliv účasti ve sportu a organizované pohybové aktivitě na sebehodnocení a kvalitu života jedinců s tělesným postižením. METODIKA: Literární zdroje byly vyhledávány prostřednictvím informačních databází Pubmed, Sport Discus, Medline, APAQ archives a European Journal of Adapted Physical Activity archives z let 1990–2009 a vybírány podle zaměření na analýzu vztahů mezi sebehodnocením, kvalitou života a pohybovou aktivitou a sportem u jedinců s tělesným postižením. Vyhledávání podle stanovených klíčových slov odhalilo 274 článků. Celkem 40 z nich obsahovalo úplné a validní informace k požadované analýze. Pro komparační analýzu výsledků bylo použito 9 z nich. Články byly rozděleny a diskutovány podle ověřovaných hypotéz. Při zjišťování trendů byly akceptovány a zviditelněny kulturní odlišnosti. Zjištěné trendy byly srovnávány s výsledky obdobně zaměřených studií u jedinců bez pohybových omezení. VÝSLEDKY: Napříč srovnávanými výsledky diskutovaných článků byl potvrzen pozitivní vztah mezi pohybovou aktivitou, účastí ve sportu a vyšším sebehodnocením. Zjištěny však byly kulturní odlišnosti v sebehodnocení tělesně postižených jedinců. V západních zemích byl zjištěn výrazně pozitivní vztah mezi pohybovou aktivitou, účastí ve sportu a vyšším sebehodnocením jedinců s tělesným postižením. Avšak ve východních zemích není tento vztah jednoznačně pozitivní. Nejednoznačnost vztahu v pracích z "východních" zemí lze vysvětlit obecně nižším sebehodnocením jedinců s tělesným postižením oproti vyspělým západním zemím s vyšší kulturní diverzitou. Fenomén soutěžení a soupeření v pohybové aktivitě a sportu nemá výrazný vliv na sebehodnocení jedinců s tělesným postižením. Pouze sportovci s tělesným postižením na vrcholové úrovni vykazují výrazně vyšší sebehodnocení než ostatní skupiny stejně postižených jedinců. Stejné trendy byly zjištěny u jedinců bez tělesného postižení ve studiích z vyspělých západních zemí. ZÁVĚRY: Z výsledků je patrné, že pohybovou aktivitou a zapojením do sportovních programů lze zvýšit sebehodnocení jedinců se specifickými pohybovými potřebami a přispět k jejich vyšší kvalitě života. Při tvorbě pohybových programů pro jedince s tělesným postižením je však nutné zohledňovat kulturní specifika. Výsledky studií potvrzují teorii úspěšnosti v životě sportovců s tělesným postižením a skutečnost, že pohybové programy mohou propojit soutěžní a dovednostní úroveň jedinců.]